Analysis of the use of rubber waste to improve the performance of the asphalt concrete mixture against tidal floods. Issue 1 (April 2021) - Martina, N; Rinawati,; Hasan, M F R; Setiawan, Y; Yanuarini, E
Abstract: The increasing rainfall can increase sea level, which increases the frequency of tidal flooding. The effects of tidal floods can emerge directly or indirectly, and the direct effects are the damage to people's houses and infrastructure. Seawater puddles due to tidal floods have inundated road infrastructure. Meanwhile, humidity in asphalt is an essential factor affecting the durability of asphalt pavement. The asphalt concrete mixture requires a proper mixture to increase durability and life. The addition of used tire powder to the asphalt mixture can increase the asphalt pavement's resistance to the effects of tidal flooding. The steps of this research include the preparation of materials, testing materials (coarse aggregate, fine aggregate, and asphalt), manufacturing of test objects with and without added materials rubber waste, the immersion of test specimens for 0 and 4 days, Marshall Stage 1 and Stage 2 testing, density testing, wheel tracking test. The results show that the effect of tidal floodwater immersion in the asphalt mixture decreases the strength and quality of the asphalt mixture, the skid resistance, which can be seen from the decreased stability and increased flow. The addition of crumb rubber to the asphalt mixture can reduce the decline in stability value, increase flow value, and better skid resistance results. The Wheel Tracking Machine test results show the effect of adding crumb rubber to the asphalt mixture to reduce the deformation speed of the asphalt mixture.